34 Search for the association of polymorphisms in inhibin alpha and prolactin genes with sperm quality in Russian Holstein bulls. (30th November 2020) - Nikitkina, Elena; Krutikova, Anna; Musidray, Artem; Anipchenko, Polina
Abstract: The formation and functioning of the animal reproductive system occurs as a result of the coordinated interaction of a wide range of genes. The hormone inhibin (INHA) is a marker of Sertoli cell function and exocrine testicular function (spermatogenesis state). The hormone prolactin (PRL) is a regulatory factor in the male reproductive system and affects gametogenesis. The aim of the work was to search for associations of inhibin alpha (INHA) and prolactin (PRL) gens polymorphism in the population of Russian Holstein bulls. Sperm traits (doublet ejaculate volume, concentration, progressive motility) were evaluated over three years of bull use and the highest rates for each trait were selected. 32 bulls had contrasting traits. DNA was isolated from semen samples. Samples were sequenced using the Applied Biosystems 3500 Genetic Analyzer using the BigDye® Terminator v3.1 Sequencing Standard Kit according to the protocol. Genotyping was then performed by PCR-RFLP. Data was analyzed using ANOVA. All pairwise multiple comparison between means were conducted by t-test. No polymorphism was detected in two regions of the PRL gene. The frequency of genotype AA in INHA gene was 0.813, the genotype AG -0.187. The GG genotype has not been identified. Bulls with the genotype AG had a higher concentration of cells (1.64 ± 0.093 billion/ml) than bulls with the genotype AA (1.35 ± 0.058) (P˂0.05). No significant differences were found in the volume of ejaculate and motility. But bulls with the AG genotype had greater ejaculate volume and motility than bulls with the AA genotype. The study of polymorphism in the genes that determine the formation and functioning of the reproductive system will help to understand the basics of these processes, as well as use them as molecular genetic markers for culling young bulls according to sperm quality. Project № АААА-А18-118021990006-9.